2020
DOI: 10.1002/ange.201913708
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Polyphenylene Dendron Conjugates for Surface Remodeling of Adenovirus 5

Abstract: Amphiphilic surface groups play an important role in many biological processes. The synthesis of amphiphilic polyphenylene dendrimer branches (dendrons), providing alternating hydrophilic and lipophilic surface groups and one reactive ethynyl group at the core is reported. The amphiphilic surface groups serve as biorecognition units that bind to the surface of adenovirus 5 (Ad5), which is a common vector in gene therapy. The Ad5/dendron complexes showed high gene transduction efficiencies in coxsackie‐adenovir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
0
3
0
3
Order By: Relevance
“…Recently, Wagner and colleagues described the preparation of amphiphilic polyphenylene dendron conjugates bearing on the surface of alternative hydrophilic (sulfonic acid) and lipophilic (propyl) groups. This surface construction serves as a biorecognition unit that bind to the surface of adenovirus 5 (Ad5), and provides high gene transduction efficiencies and high-protein binding capacity [ 92 ]. The pattern of the amphiphilic polyphenylene dendron originated from desymmetrization of amphiphilic polyphenylene dendrimers.…”
Section: Dendrimers Used In Covid-19 Treatment: Few Clinical Examples But Limitless Possibilitiesmentioning
confidence: 99%
“…Recently, Wagner and colleagues described the preparation of amphiphilic polyphenylene dendron conjugates bearing on the surface of alternative hydrophilic (sulfonic acid) and lipophilic (propyl) groups. This surface construction serves as a biorecognition unit that bind to the surface of adenovirus 5 (Ad5), and provides high gene transduction efficiencies and high-protein binding capacity [ 92 ]. The pattern of the amphiphilic polyphenylene dendron originated from desymmetrization of amphiphilic polyphenylene dendrimers.…”
Section: Dendrimers Used In Covid-19 Treatment: Few Clinical Examples But Limitless Possibilitiesmentioning
confidence: 99%
“…The strong binding energy of these interactions [32] led to conformational changes of the adsorbed proteins [17,[19][20][21][22]. On a similar line, it was demonstrated that the amphiphilic surface was able to effectively bind to another virus (adenovirus 5) through the virus capsid proteins [33]. In a recent study, it was revealed that the hydrophobic phenylalanine residue of the SARS-CoV-2 spike protein was responsible for the strong bonding with the angiotensin-converting enzyme 2 (ACE2) receptor for the entry to the host cells [34].…”
Section: Strategies Of the Surface Engineering/ Modificationmentioning
confidence: 99%
“…Установлено, что «корона» из амфифильных полифениленовых дендримеров уменьшала связывание липосомами определенных опсонинов и увеличивала адсорбцию белков, контролирующих клеточное поглощение [45]. Эти же авторы провели серию исследований по изучению возможности использования амфифильных дендронов в качестве единиц биораспознавания вирусов [46]. Обнаружено, что поверхностные группы амфифильных дендримеров могут связываться с аденовирусом 5 (Ad5), который является распространенным вектором в генной терапии.…”
unclassified
“…Поверхности, покрытые этими дендронами, были проанализированы на предмет их связывающей способности с белками крови, что важно для прогнозирования их характеристик в кровотоке. Таким образом, авторами разработана новая платформа для введения биоактивных групп на поверхность Ad5 без химического изменения вирусных частиц [46]. Мажораль с соавт.…”
unclassified
See 1 more Smart Citation